A Concise History of Asperger Syndrome: The Short Reign of a Troublesome Diagnosis - Barahona-Corrêa, J. B.; Filipe, Carlos N. (Frontiers in Psychology, 2016)
First described in 1944 by Hans Asperger (1944), it was not before 1994 that Asperger Syndrome (AS) was included in the fourth edition of the Diagnostic and Statistical Manual of Mental Disorders, only to disappear in the Manual’s fifth edition in 2013. During its brief existence as a diagnostic entity, AS aroused immense interest and controversy. Similar to patients with autism, AS patients show deficits in social interaction, inappropriate communication skills, and interest restriction, but also display a rich variety of subtle clinical characteristics that for many distinguish AS from autism. However, difficulties operationalising diagnostic criteria and differentiating AS from autism ultimately led to its merging into the unifying category of Autistic Spectrum Disorders. Here we briefly review the short history of this fascinating condition.